A second-order adaptive temporal-causal network model for age and gender differences in evolving choice of emotion regulation strategies. Issue 2 (2nd April 2020) - Ullah, Nimat; Gao, Zhenyu; Liu, Rui; Treur, Jan
ABSTRACT: Emotion being an essential part of one's life, its regulation is of utmost importance. The choice of strategies that one employs for regulating their emotions, varies at various stages of their lives and with contexts. Similarly, gender also has an influence on the choice of emotion regulation strategies. This paper presents a second-order adaptive network model for this phenomenon where the choice of strategies varies with age and gender in an adaptive manner. Simulation results for both the genders (male and female) have been provided where for both the genders, choice of emotion regulation strategies changes as age increases. The second-order adaptive network model presented here extends a non-adaptive network model previously introduced at ICCCI'19.